2014
DOI: 10.1063/1.4881457
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric function of Si1−xGex films grown on silicon-on-insulator substrates

Abstract: The dielectric functions of undoped and P-doped Si1−xGex (SiGe) films with a compressive strain on silicon-on-insulator (SOI) substrates are obtained by using spectroscopic ellipsometry. The respective Kato–Adachi and Tauc–Lorentz models are best fitted to the undoped and P-doped SiGe films to obtain their complex dielectric functions. The undoped SiGe films are characterized by multimodal peaks in the dielectric function, whereas the P-doped SiGe films exhibit only a broad peak. Further, the E0 and E1 critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In parallel, it has been suggested that SOI could behave as a compliant substrate which could suppress the development of the ATG instability and allow full strain relaxation by fluency gliding at the interface 19 24 . Epitaxial SiGelayers on buried oxide are then under intense scrutiny due to their applications in ultra-scales performance-augmented CMOS transistors 25 29 . The aim is to pursue the Moore’s law by developing planar transistors based on ultra-thin Si/SiGe or pure Ge nanochannels on insulator (UTSGOI or UTGOI) systems 30 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, it has been suggested that SOI could behave as a compliant substrate which could suppress the development of the ATG instability and allow full strain relaxation by fluency gliding at the interface 19 24 . Epitaxial SiGelayers on buried oxide are then under intense scrutiny due to their applications in ultra-scales performance-augmented CMOS transistors 25 29 . The aim is to pursue the Moore’s law by developing planar transistors based on ultra-thin Si/SiGe or pure Ge nanochannels on insulator (UTSGOI or UTGOI) systems 30 34 .…”
Section: Introductionmentioning
confidence: 99%